ANALISIS KUALITAS PELAYANAN PUBLIK DI BADAN LINGKUNGAN HIDUP KOTA SEMARANG - Widya Anita; Herbasuki Nurcahyanto (Journal of Public Policy and Management Review, 2016)
Environment Agency Semarang is one of the technical institutions of local government has a fundamental duty to implement the preparation and implementation of policies that are specific areas in the environmental field. To carry out the basic tasks of the Environmental Agency of Semarang has a function which is one implementation of government affairs and public services in the environmental field. Quality of service can be determined by comparing the service that has been given to indicators measuring the quality of service. Quality of service can be said to be good if in accordance with the expectations of society. To measure the quality of service in Semarang city environmental agency used five indicators such as tangible, reliability, responsiveness, assurance and empathy.. The purpose of this research was analyze the quality of public services at the Environment Agency of Semarang to the public so that people feel the need basically is to get a good service from government acceptable and achieve maximum satisfaction. This research is using descriptive qualitative research design with informants from the employees in environmental agency and publicathat propose services